Research publication in long term athlete development: a systematic review and bibliometric analysis of Scopus database in 2009 – 2023 - Muchamad Arif Al Ardha; Nurhasan Nurhasan; Lutfi Nur; Ahmad Chaeroni; Kolektus Oky Ristanto; Nur Shanti Retno Pembayun; Chung Bing Yang; Ju Han Lin; Kukuh Pambuka Putra; Nur Salsabila Rhesa Pandhadha Putra; Sauqi Sawa Bikalawan; Ainun Zulfikar Rizki; et al. (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study inquired about Long-Term Athlete Development (LTAD) research development and impact. The study was conducted using a bibliometric analysis and systematic review. There were 100 top citation research articles published between 2009 to 2023 and selected from SCOPUS research journal databases by using the keywords "Long Term Athlete Development" and “LTAD”. Furthermore, 10 top citation articles were further investigated by systematic review methods. The study outlines the predominance of journal articles as the main conduit for LTAD discourse, with a notable average citation rate underscoring their influence. The United Kingdom (UK) leads in contributions and citations. The geographical distribution showcases the global engagement and diverse perspectives within LTAD research. The examination reveals an initial focus on fundamental sports training and coaching roles, progressively expanding to include practical LTAD applications, demographic, social dynamics, and physiological nuances. This trajectory demonstrates a multidisciplinary approach that integrates several aspects of athlete development. It also emphasizes the need for more thorough longitudinal research to provide empirical support for the principles of LTAD in a variety of cultural and athletic contexts. Even with the breadth of research, empirical, longitudinal studies are still required to confirm the effectiveness of LTAD models in a variety of cultural and sports contexts. The review calls for enhanced international collaboration to further consolidate LTAD research and practice, advocating for a holistic and inclusive understanding of athlete development that integrates gender and social inclusion.